Redressing Historical Bias: Exploring the Path to an Accurate Representation of the Past - Rashid Manzoor Bhat; P. Rajan; Lakmini Gamage (Journal of Social Science, 2023)
The study examines the role of historical bias and the ways in which it can be addressed to achieve a more accurate representation of the past. The study aims to identify the factors that contribute to historical bias, the impact it has on our understanding of history, and the strategies that can be employed to overcome it. The study employs a mixed-methods approach that includes a comprehensive review of relevant literature, interviews with scholars and historians, and analysis of historical narratives. The study finds that historical bias is perpetuated by a variety of factors, including political and cultural agendas, the limitations of available evidence, and the perspectives and biases of historians themselves. The study also identifies several strategies that can be used to address historical bias, including the adoption of a more diverse and inclusive approach to historical research, the incorporation of multiple perspectives and sources, and the acknowledgement of historical injustices and their impact on marginalized groups. The study concludes that a commitment to redressing historical bias is necessary to achieve a more accurate and inclusive representation of the past, which can in turn contribute to a more just and equitable society.